Persepsi Pemilik Lahan Terhadap Faktor – Faktor Yang Mempengaruhi Penggunaan Tenaga Kerja Usaha Tani Hortikultura Di Kabupaten Kerinci - Sandi Kurniawan; Zul Azhar; Sri Ulfa Sentosa (Universitas Negeri Padang, 2022)
The agricultural sector aims to expand job opportunities and support regional development, which is very helpful for the benefit of the wider community, especially providing job opportunities by absorbing labor. This research is classified as descriptive and inductive research by examining the influence between the independent variable and the dependent variable using data analysis techniques, namely multiple linear regression analysis. The results of the analysis show that: (1) wages have a significant effect on the use of labor, (2) education has a significant effect on the use of labor, (3) technology has a significant effect on the use of labor, (4) capital has a significant effect on the use of labor, (5) wages, education, technology and capital simultaneously have a significant effect on the use of labor.